Cationic Chains of Parent Arsanylboranes and Substituted Phosphanylboranes1. Issue 47 (31st July 2017) - Marquardt, Christian; Balázs, Gábor; Baumann, Josef; Virovets, Alexander V.; Scheer, Manfred
Abstract: The substituted monomeric phosphanylboranes Ph2 P−BH2 ⋅ NMe3 (1 ) and t BuHP−BH2 ⋅ NMe3 (2 ) have been used for the synthesis of cationic chain compounds built up by R2 P−BH2 units. With a simple synthesis route, the highly stable cations [Me3 N⋅ H2 B−PR1 R2 −BH2 ⋅ NMe3 ] + (1 a, 2 a ) and [Me3 N⋅ H2 B−PR1 R2 −BH2 −PR1 R2 −BH2 ⋅ NMe3 ] + (1 b, 2 b ) (R1 =R2 =Ph; R1 =H, R2 = t Bu) are obtained as iodide (I − ) salts. The reaction of H2 As−BH2 ⋅ NMe3 (3 ) with IBH2 ⋅ SMe2 leads to [Me3 N⋅ H2 B−AsH2 −BH2 −AsH2 −BH2 ⋅ NMe3 ][I] (3 a ), the longest so far known arsanylborane chain. Compound3 a reacts with acetonitrile through a formal hydroarsination reaction to form [cyclo‐{As(BH2 ⋅ NMe3 )(CMe=NH)2 (BH2 )}][I] (4 ). The reported synthetic strategy has proved to be a powerful tool for the formation of small, cationic oligomeric units. All products were comprehensively characterized by X‐ray structure analysis, NMR, IR spectroscopy, and mass spectrometry in cooperation with DFT calculations. Abstract : Cationic inorganic chains : The synthesis of oligomeric, cationic group 13/15 compounds was successfully extended to organosubstituted phosphanylboranes. Furthermore, the longest so far known chain with a backbone consisting of alternating B and As atoms was obtained, which was converted into a heterocycle by a hydroarsination reaction with acetonitrile.